Simultaneously Recovering High-Purity Chromium and Removing Organic Pollutants from Tannery Effluent - Jie Zong; Yan-Chun Li; Kang Hu (Journal of Chemistry)
Chromium pollution is a serious issue because of carcinogenic toxicities of the pollutants and low recovery rate of chromium because of the presence of organic, such as protein and fat. In this work, high recovery rate and high purity of the chromium ion were successfully prepared by the way of acid enzyme, flocculant, and Fenton oxidation. The experiments were characterized by TG, TOC, UV-VIS, and SEM. In the work, the tannery waste chrome liquor was used as experimental material. The results showed that the percentage of reduction of TOC in the tannery waste chrome liquor by method of Fenton oxidation, acid enzyme, and the flocculant was 71.15%, 65.26%, and 22.05%, respectively. Therefore, the organism content of chrome tanning waste liquid was greatly reduced through the pretreatment. And the application experiment showed that the properties and grain surface and fibers of the tanned leather with commercial chromium powder and chrome tanning agent prepared from the chromium waste liquid treated with Fenton are nearly the same.